Incorporating Outside Sources in Kurdish EFL Students’ Academic Writing - Brime, Asma Abas; Bajalan, Fatimah Rashid Hassan (European Scientific Journal, ESJ, 2017)
In academic writing, students need to incorporate outside sources. Incorporated sources involve summarizing, paraphrasing, and quoting. Depending on why the source is being used, one method may be more appropriate than another. All three methods of incorporating sources require citations. Sources can be utilized for various purposes: presenting facts or statistics, serving as evidence to support an argument, lending authority to an argument or idea, i.e., authoritative discourse, providing examples and illustrations, stating an opposing viewpoint, and so on. For every source, students must determine the purpose of that source and how to best incorporate it into their writing. Both aspects are crucial to effectively integrating sources throughout the paper. Effective integrating of the sources in the EFL writing is a demanding task. Therefore, the aim of the study is to find out the difficulties and challenges the students face while using outside sources in academic writing. In achieving the aim of this study, twenty five third-year students were given an assignment to write an essay in which they had to incorporate an outside source. The study was conducted in the first semester in the academic year 2016-2017. Discussion of findings, implications and recommendations were presented after analyzing the students’ works.